Citrullinated α-enolase is an effective target for anti-cancer immunity - Cook, Katherine; Daniels, Ian; Symonds, Peter; Pitt, Tracy; Gijon, Mohamed; Xue, Wei; Metheringham, Rachael L.; Durrant, Lindy; Brentville, Victoria A. (Taylor & Francis, 2018)
Targeting post-translationally modified epitopes may provide a new strategy for generating tumor specific immune responses. Citrullination is the post-translational modification of arginine to citrulline catalyzed by peptidylarginine deaminase (PAD) enzymes. Presentation of citrullinated peptides on MHC-II has been associated with autophagy. Tumors upregulate autophagy and present citrullinated peptides in response to stresses including nutrient deprivation, oxygen deprivation, redox stress and DNA damage, making them good targets for immune attack. The ubiquitous glycolytic enzyme α-enolase (ENO1) is often citrullinated and degraded during autophagy. Immunization of mice with two citrullinated ENO1 peptides (ENO1 241-260cit253 or 11-25cit15) induced strong Th1 responses that recognize the post-translationally modified, but not the wild type unmodified epitope. ENO1 11-25cit15 induced tumor therapy of melanoma cells in C57Bl/6 (B16F1 50% survival p = 0.0026) and ENO1 241-260cit253 in HLA-DR4 transgenic mice (B16-DR4 50% survival p = 0.0048). In addition, ENO1 241-260cit253 induced therapy of pancreatic (Pan02-DR4 50% survival p = 0.0076) and lung (LLC/2-DR4 40% survival p = 0.0142) tumors in HLA-DR4 transgenic mice. The unmodified epitope induced no anti-tumor response. Minimal regression of class II negative B16 or LLC/2 tumor was seen, confirming direct recognition of MHC-II was required. Most tumors only express MHC-II in the presence of IFNγ; an IFNγ inducible model showed strong responses, with rejection of tumors in up to 90% of animals (p = 0.0001). In humans, a repertoire to ENO1 241-260cit253 was observed in healthy donors. This response was CD4 mediated and seen in people with a variety of HLA types suggesting a broad application for this vaccine in human cancer therapy.